Adolescents with Persistent Symptoms Following Acute SARS-CoV-2 Infection (Long-COVID): Symptom Profile, Clustering and Follow-Up Symptom Evaluation - Marco Floridia; Danilo Buonsenso; Laura Macculi; Liliana Elena Weimer; Marina Giuliano; Flavia Pricci; Leila Bianchi; Domenico Maurizio Toraldo; Graziano Onder; The ISS Long-COVID Study Group (Children)
Background: Few studies have evaluated long-COVID in adolescents. Methods: Cohort study. Demographics, clinical data, and the presence of 30 symptoms were collected with a modified WHO form. Mean values were compared by Student’s t test and proportions by the chi-square test or Fisher test, with trends over time analysed using the chi-square test for trend. Potential risk factors independently associated with persisting symptoms were evaluated in a multivariable logistic regression model. Clustering of cases was analysed by two-step automatic clustering. Results: A total of 97 adolescents aged 12–17 (54.6% females, 45.4% males) were evaluated. After a mean interval of 96 days (SD 52) from acute infection, the mean number of symptoms (2.8 overall) was higher for pre-Omicron (3.2 vs. 2.5 in Omicron, p = 0.046) and moderate/severe acute infections (4.2 vs. 2.7 in mild, p = 0.023). Fatigue (62.9%) and dyspnea (43.3%) were the most common symptoms, followed by headache (28.9%), thoracic pain (22.7%), diarrhea (20.6%), palpitations/tachycardia (17.5%), articular pain (15.5%), difficult concentration (14.4%), muscle pain (12.4%), taste reduction (8.2%), smell reduction (8.2%), fever (6.2%), and skin disorders (5.2%). The symptom profile was similar in males and females but showed significant differences from that observed in concurrently followed adults. After a mean interval of 340 days from infection, 45.3% still presented symptoms, with persistence associated with higher number of initial symptoms. Two clusters were defined that differed in the phase of acute infection and the number and profile of symptoms. Conclusions: Long-COVID manifestations in adolescents may differ from those observed in adults. Polisymptomaticity may predict long-term persistence.